Managing Risks for a Safer Built Environment in Malawi : Building Regulatory Capacity Assessment - World Bank Group (World Bank, Washington, DC, 2019)
In a rapidly urbanising world, Malawi remains one of the least urbanised countries in Africa. Approximately 16.7 percent of Malawi's population live in urban areas. Nevertheless, the country is urbanising at a moderate rate of approximately 3.7–3.9 percent per year. If growth continues at this rate, by 2030, approximately 20 percent of the population will be city dwellers, reaching 30 percent in 2050. This urban growth has the potential to improve economic opportunities and living conditions across Malawi. This is particularly significant given that approximately 69 percent of the population are living under the international poverty line of 1.9 US Dollars/day in purchasing power parity terms. However, challenges are also associated with this shift and concentration of population. With urbanisation comes a substantial amount of new construction. In Malawi, much of this new construction has occurred in cities and towns with limited capacity to ensure the structures in which people live, work and gather are safely sited and built to withstand chronic stresses (i.e. fire and spontaneous collapse) and disaster shocks (i.e. earthquakes and floods). In Lilongwe, for example, estimates indicate that 76 percent of residents live in informal settlements. These settlements are generally characterised by a lack of access to publicservices, tenure insecurity and inadequate housing. Malawi is impacted by a wide range of hazards, particularly droughts, floods, landslides, wildfires and earthquakes. Malawi is also vulnerable to recurrent and chronic risks. Large building fires in recent years include the LL and Mchinji Markets and the Mulanje Bus Depot in 2016 and the Area 13 and Zomba Market in 2018. In many ways, Malawi is at a crossroads: the regulatory decisions made now will significantly impact the longterm safety, productivity and resilience of the built environment in rural and urban areas. With its low base and moderate rate of urbanisation, Malawi is wellpositioned to formulate plans to maximise the benefits and to manage the challenges of urban agglomeration.